2017
DOI: 10.1136/bmjopen-2017-019199
|View full text |Cite
|
Sign up to set email alerts
|

Early low-energy versus high-energy enteral nutrition support in patients with traumatic intracerebral haemorrhage: protocol for a randomised controlled trial

Abstract: BackgroundEarly enteral nutrition (EN) is associated with shorter hospital stay and lower infection and mortality rates in patients with intracerebral haemorrhage. However, high-energy support always causes clinical complications, such as diarrhoea and aspiration pneumonia, and the true benefit of high-energy support in these patients has not been investigated. The appropriate amount of energy support still needs further investigation. Therefore, we are performing a randomised controlled trial to investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…6 However, numerous neurologically injured patients fail to achieve the target energy intake because of delayed gastric emptying and decreased tone of the lower esophageal sphincter. 2 In this regard, the results of 2 cluster, randomized controlled trials indicated no reduction in mortality in the patients receiving higher EN compared to the group receiving routine care. 7 On the other hand, some clinical studies have demonstrated that energy restriction may be beneficial, since it affects the longevity biomarkers, insulin sensitivity, metabolic inflammation, and oxidative stress.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…6 However, numerous neurologically injured patients fail to achieve the target energy intake because of delayed gastric emptying and decreased tone of the lower esophageal sphincter. 2 In this regard, the results of 2 cluster, randomized controlled trials indicated no reduction in mortality in the patients receiving higher EN compared to the group receiving routine care. 7 On the other hand, some clinical studies have demonstrated that energy restriction may be beneficial, since it affects the longevity biomarkers, insulin sensitivity, metabolic inflammation, and oxidative stress.…”
Section: Introductionmentioning
confidence: 98%
“…The brain is a major, complex body organ, and its injury could largely affect the quality of life and impose an economic burden because of the associated healthcare issues. 1,2 In neurocritical care units, nutrition support is of utmost importance, since a critical neurologic insult may be followed by hypermetabolic and hypercatabolic responses. 3 According to Seule et al, early enteral nutrition (EN) is associated with clinical benefits, such as improved hypercatabolic state, muscle-mass loss, and infections.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations